2016
DOI: 10.1055/s-0036-1584824
|View full text |Cite
|
Sign up to set email alerts
|

Update on Postsurgical Scar Management

Abstract: Postoperative scar appearance is often a significant concern among patients, with many seeking advice from their surgeons regarding scar minimization. Numerous products are available that claim to decrease postoperative scar formation and improve wound healing. These products attempt to create an ideal environment for wound healing by targeting the three phases of wound healing: inflammation, proliferation, and remodeling. With that said, preoperative interventions, such as lifestyle modifications and optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 35 publications
0
37
0
3
Order By: Relevance
“…Commander et al . (2016) reported petrolatum to increase epithelialisation and decrease scarring in people, while an experimental study in dogs reported that wounds dressed with petrolatum‐containing dressings contracted more quickly in the first 7 days and had less epithelialisation than wounds dressed with cotton non‐adherent dressings (Lee et al . 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Commander et al . (2016) reported petrolatum to increase epithelialisation and decrease scarring in people, while an experimental study in dogs reported that wounds dressed with petrolatum‐containing dressings contracted more quickly in the first 7 days and had less epithelialisation than wounds dressed with cotton non‐adherent dressings (Lee et al . 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of patient education and mutual communication between patients and care providers in the preoperative period can help achieve more effective scar care and ensure continuity of treatment from the postoperative period to the completion of wound healing. 27 In realistic situations, it is clear that patients with normal or problematic scars frequently experienced psychological distress (anxiety and depression) and chronic symptom (scar tissue pain and itching). Minimising changes of appearance in scarring as well as enhancing patient satisfaction can contribute to improving the quality of life in patients' daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, although numerous treatments exist, no single modality has been proven superior over others. [101] Evidence in pediatric patients indicates that Asian patients have a three-fold increased rate of hypertrophic scarring relative to Caucasians.…”
Section: Resultsmentioning
confidence: 99%